Electric field modification of magnetotransport in Ni thin films on (011) PMN-PT piezosubstrates - Tkach, Alexander (2017)
This study reports the magnetotransport and magnetic properties of 20 nm-thick polycrystalline Ni films deposited by magnetron sputtering on unpoled piezoelectric (011) [PbMg1/3Nb2/3O3](0.68)-[PbTiO3](0.32) (PMN-PT) substrates. The longitudinal magnetoresistance (MR) of the Ni films on (011) PMN-PT, measured at room temperature in the magnetic field range of -0.3T < mu H-0 < 0.3 T, is found to depend on the crystallographic direction and polarization state of piezosubstrate. Upon poling the PMN-PT substrate, which results in a transfer of strain to the Ni film, the MR value decreases by factor of 20 for the current along [100] of PMN-PT and slightly increases for the [01 (1) over bar] current direction. Simultaneously, a strong increase (decrease) in the field value, where the MR saturates, is observed for the [01 (1) over bar] ([100]) current direction. The anisotropic magnetoresistance is also strongly affected by the remanent strain induced by the electric field pulses applied to the PMN-PT in the non-linear regime revealing a large (132 mT) magnetic anisotropy field. Applying a critical electric field of 2.4 kV/cm, the anisotropy field value changes back to the original value, opening a path to voltage-tuned magnetic field sensor or storage devices. This strain mediated voltage control of the MR and its dependence on the crystallographic direction is correlated with the results of magnetization reversal measurements. (C) 2015 AIP Publishing LLC.